Development of experiment module using physics virtual labs application in optics subject studies for secondary high school students - Fikri, Geri Haidar; Ervina, Eka; Nursulistiyo, Eko (AIP conference proceedings, 2022)
Practicum is an activity that is very important in the physics learning process. In this era of information and technology, many physics simulations can be used in the learning process. These simulations are applications on Android that can be accessed quickly and downloaded for free in the google play store. This opportunity can be used to improve the existing learning process in schools. But how to use this simulation in the learning process is not widely known. We need a study to develop an experimental module using this simulation. The main objective of this study is to create a practical module using a virtual physics laboratory on optical material for junior high schools. The stages of development are needed analysis, preliminary design, validation by experts (learning technology experts and subject matter experts), and product trials by users or student’s responses. The virtual laboratory-based learning module that has been developed is classified as very feasible. This shows that these products can be used to support the learning process of grade VIII students. The result is supported by the average respondents’ assessment of 82% in the “very good” category. This assessment was obtained from the results of the learning material expert’s evaluation of 83% in the “very good” category, 70% of media experts in the “good” category, 85% of colleagues in the “very appropriate” category, User of 81% in the “very good” category, and student responses of 82% in the “very good” category. It is concluded that the physics learning module using the Physics Virtual Lab application is suitable for use as a learning module for junior high school students.